BK virus in kidney transplantation: A single center experiences - Gokhan Ertugrul; Tumay Yanaral (Archives of Organ Transplantation - Peertechz Publications, 2019)
Background: BK virus is the most common infectious causes of nephropathy and graft loss after kidney transplantation. In our study, we investigated the factors that may affect positive BK virus in the blood in patients with kidney transplantation. Material and method: Between April 2014 and April 2017 at Medipol University Medical Faculty Hospital Organ Transplantation Department, Istanbul, Turkey, 30 patients with positive BK virus in urine after kidney transplantation were studied retrospectively. In these patients were divided into two groups; Group 1: Patients with BK virus positive in the blood. Group 2: Patients with BK virus negative in the blood. Between these two groups, factors that may affect positivity in blood were compared.